Analisa Tingkat Kepatuhan WPOP Terhadap Penerimaan Pajak Penghasilan Pada KPP Pratama Jakarta Duren Sawit - Dedi Suharyadi (Universitas Bina Sarana Informatika, 2019)
Abstract - Taxes are still one of the largest state revenues that will be used to finance development and also increase welfare for all Indonesians. To be able to achieve the target of tax revenue, awareness and compliance must be fostered for the community, in this case a taxpayer to fulfill tax obligations in accordance with applicable regulations. The purpose of this study is to find out how the level of compliance of individual taxpayers towards income tax receipts at KPP Pratama Jakarta Duren Sawit. The research method used is by conducting data comparisons for each year, literature studies sourced in several literature. The results showed that the level of taxpayer compliance in reporting annual tax returns in 2013 amounted to 53.21%, in 2014 it rose to 57.61%, in 2015 again increased by 69.14%, in 2016 again increased by 73.60% and in 2017 the increase was quite significant because the level of compliance reached 90.64%. Viewed from the side of achievement compared to the income tax revenue target the level of achievement can be said to be up and down. But seen from the amount of income tax revenue from 2013 to 2017, it tends to increase. Keywords: Obedience, Tax Receipts, Taxpayer